2018
DOI: 10.3390/ijms19113662
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Glycemic Index, Glycemic Load, and Dietary Antioxidant Capacity with Insulin Resistance in Subjects with a Cardiometabolic Risk Profile

Abstract: Background: Dietary total antioxidant capacity (TAC), glycemic index (GI), and glycemic load (GL) are accepted indicators of diet quality, which have an effect on diet–disease relationships. The aim of this study was to evaluate potential associations of dietary TAC, GI, and GL with variables related to nutritive status and insulin resistance (IR) risk in cardiometabolic subjects. Methods: A total of 112 overweight or obese adults (age: 50.8 ± 9 years old) were included in the trial. Dietary intake was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Standardised questionnaires were used to evaluate all the variables. Dietary practices were evaluated using a semi-quantitative 96-item questionnaire called Food Frequency Questionnaire (FFQ), validated in Spanish adults [ 12 , 13 ]. Each item included a typical portion size.…”
Section: Methodsmentioning
confidence: 99%
“…Standardised questionnaires were used to evaluate all the variables. Dietary practices were evaluated using a semi-quantitative 96-item questionnaire called Food Frequency Questionnaire (FFQ), validated in Spanish adults [ 12 , 13 ]. Each item included a typical portion size.…”
Section: Methodsmentioning
confidence: 99%
“…The dietary total antioxidant capacity (TAC) score was calculated by computing the individual TAC values from the ferric reducing antioxidant power assay of each food. The mean TAC value of the foods contained in each item was used to calculate the dietary TAC score from the FFQ [31].…”
Section: Dietary Intake Estimatementioning
confidence: 99%
“…Glycemic index (GI) values for single food items on the food frequency questionnaire were derived from the "International Tables of Glycemic Index and Glycemic Load Values" as previously reported [31]. Total dietary GI was estimated by multiplying the amount of available carbohydrate (g) of each food item by its GI.…”
Section: Dietary Intake Estimatementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the composition of the diet may have an important role in the management of NAFLD [ 36 ], since the severity of NAFLD has been associated with an increase in oxidative stress and pro-inflammatory status [ 37 ]. Indeed, specific foods such as meat [ 38 ], fruits [ 39 ], glycemic index [ 40 ] or protein content [ 41 ] have been involved on pro-oxidative and antioxidant patterns in liver patients. Furthermore, lifestyle factors have been associated with NAFLD in a Mediterranean cohort [ 42 ], which have repeatedly reported that physical activity, exercise and sport practice are related to oxidative stress [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%